Preparation method of V2O5 by vapour carbonizing pretreatment of vanadium-containing stone coal - ZHANG SHUNXI; CHENG XIANZHONG (2017)
The invention relates to a preparation method of V2O5 by vapour carbonizing pretreatment of vanadium-containing stone coal. The technical scheme comprises steps of smashing a vanadium-containing stone coal raw material to 100-200 meshes by a ball mill; mixing the mineral powder and concentrated sulfuric acid evenly in the ratio of 1: (0.2-0.4), and then adding 8-15% of 0.5-5 g/L of initiator solution in the mixture, and stirring for 20-30 min. A wet sand shaped mixture after stirring is loaded to a hopper truck through a conveying belt, and then pushed to a vapor carbonizing room to carbonize at 150-250 DEG C. The carbonized slag is performed with a two-stage process to leach vanadium according to the solid-to-liquid ratio of 1: (1-2), and the filtrate is blue solution; then over 99.5% vanadium pentoxide product can be obtained according to the preparation method of V2O5 by regular hydrometallurgy. The preparation method is free from ore roasting process and generation of waste gas, and is simple in process,